Feasibility and Added Value of the Robusta Coffee Agroindustry in Kebun Tebu District, West Lampung - Analianasari, Analianasari; Shintawati, Shintawati; Berliana, Dayang; Sari, Shania Puspita (P3M Politeknik Negeri Jember, 2024)
The study aims to identify the characteristics of the ground coffee industry products, feasibility, and the added value of ground coffee in the Kebun Tebu District of West Lampung. The research method that the ground coffee industry will use in the Kebun Tebu sub-district uses qualitative descriptive analysis to identify the feasibility of the ground coffee business using the R/C and B/C ratio indicators, and the amount of added Value resulting from ground coffee processing is calculated using the Hayami method. The research results show that Coffee bean processing activities are financially feasible for the West Lampung Kebun Tebu industry to undertake and continue. They are also feasible for the community because they are economically profitable. Feasibility analysis based on the R/C and B/C ratio indicators shows that the ground coffee business with honey and natural processes has R/C > 1 and B/C > 0 or is worthy of business. The added value resulting from natural and processed ground coffee honey is classified as having a high value-added ratio because the Value added ratio is >40 percent, and processing ground coffee is a capital-intensive activity.